Self-Compassion on Children from Broken Homes Reviewed from Family Support and Mindfulness - Nurmayani, Marcelia Ayu; Astuti, Rr. Dwi (Manunggal Halim Jaya, 2025)
This study aims to determine the relationship between self-compassion in children from broken homes with family support and mindfulness. This study uses a quantitative approach. The sample in this study consisted of 172 respondents who were victims of broken homes. The data analysis of this study used the SPSS 15.0 application for Windows Evaluation Version. The results of the primary hypothesis test showed that the significance level of p was 0.025 (p <0.05) with Rx12y = 0.321; there was a significant relationship between family support and mindfulness with self-compassion. The results of the minor hypothesis test of self-compassion and family support showed a correlation coefficient between the two variables (Rx1y) of 0.299 with a p value of 0.006 (p <0.05). The results showed a very significant positive relationship between self-compassion and family support. The results of the minor hypothesis test of self-compassion and mindfulness showed a correlation coefficient between the two variables (Rx1y) of 0.013 with a p value of 0.459 (p <0.01). The results showed no significant positive relationship between self-compassion and mindfulness. The results of the 172 broken home victims showed that family support and mindfulness were significantly related to self-compassion (r = 0.321, p = 0.025) together, with a contribution of 10.3%. Family support was significantly related to self-compassion (r = 0.299, p = 0.006), contributing 8.9%. Meanwhile, mindfulness was not significantly related (r = 0.013, p = 0.459), with a contribution of only 0.02%. Family support was a significant factor in self-compassion development in victims of broken homes.